The Development of Assessment Instrument for Vocational High School Students' Competency Test in Automotive Occupational Positions (Journal of Vocational and Career Education, 2022)
In the development of competency assessment instruments, it becomes possible to eliminate the weaknesses of previous competency assessment instruments. It results in an ideal competency assessment that can enhance students' competencies in the Automotive Engineering program.The aim of this research is to develop an assessment instrument for vocational high school students' competency test in automotive technician positions in the professional automotive field. This research follows the Research and Development (RD) approach, specifically the ADDIE model, which stands for Analysis, Design, Development, Implementation, and Evaluation.The instrument used in this study consists of questionnaires. The questionnaires were employed to assess the validity, practicality, and to determine factor analysis. The data for the validity of the assessment instrument were collected from assessment experts (assessors), subject matter experts from the business and industrial sector (Indonesian: Dunia Usaha Dunia Industri, DUDI), and evaluation experts (lecturers). The practicality data of the assessment instrument in this research were gathered from automotive teachers at Semarang State Vocational High School 1.Based on the data analysis results, the validity test yielded a score of 4.60, which indicates a significantly valid instrument. The practicality test resulted in a 91% score, meeting the criteria for a highly practical instrument. Additionally, the factor analysis showed that the Sum of Loadings of Factors (SLF) for 60 items was ≥ 0.5, indicating that all items were proven valid. Therefore, it can be concluded that this competency assessment instrument possesses good construct validity and reliability.